Uji Efektivitas Sediaan Facial Wash Ekstrak Etanol Daun Sirsak (Anonna Muricata Linn.) Terhadap Bakteri (Propionibacterium Acnes) - Depa Sanjaya; Lina Rahmawati R; Salsabila Adlina (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Acne is a skin condition that usually appears on the face, neck, chest and back. Acne occurs when oil glands become overactive causing skin pores to clog. Soursop leaf is a type of natural ingredient that contains tannins, alkaloids, saponins, and flavonoids which function as antibacterials. This study aims to provide scientific data regarding the utilization of soursop leaf extract in facial wash preparations used as an antibacterial for Propionibacterium acnes. With concentration variations of 1%, 3% and 5%, the preparation test included pH test, homogeneity test, viscosity test, high foam test and antibacterial test. The results of this study showed that the pH test ranged from 4.5-6, the preparation was homogeneous, the viscosity was 0.82-1.91 cps, the foam height was 75-80% and for the antibacterial test of all concentration variations it did not have antibacterial inhibition due to two factors, biological factors and chemical factors. The conclusion in this study was that variations in the concentration of the ethanol extract of soursop leaves had no anti-bacterial inhibition against facial wash preparations of the ethanol extract of soursop leaves.